Association between seminal plasma neopterin and oxidative stress in male infertility: A case-control study - Tayebeh Ghiasvand; Mohammad Taghi Goodarzi; Gholamreza Shafiee; Alireza Zamani; Jamshid Karimi; Marzieh Ghorbani; Iraj Amiri (International Journal of Reproductive BioMedicine, 2018)
Background: Neopterin is a significant and sensitive marker in estimating the activity of cellular immune system. Oxidative stress plays a role in the etiology of male infertility. Increased reactive oxygen species is accompanied with increase in neopterin level. Hence neopterin may be involved in male infertility. Objective: The objective of this case-control study was to determine neopterin level in idiopathic infertile and normospermic men; furthermore, to identify its relationship with oxidative stress markers including total oxidant, malondialdehyde, sperm DNA fragmentation, and total antioxidant capacity of seminal plasma. Materials and Methods: Forty seven infertile and forty three normospermic males were selected according to WHO criteria. Their semen and blood samples were taken; subsequently, the levels of neopterin, total oxidant, total antioxidant, malondialdehyde, and sperm DNA fragmentation were measured. Results: The levels of neopterin, total oxidant, and malondialdehyde in seminal plasma of infertile males were significantly higher than those of normospermic group (p=0.038, 0.018, and 0.028, respectively). Furthermore, sperm DNA fragmentation in infertile men was higher than that of control group (p<0.001). Moreover, total antioxidant capacity of seminal plasma in infertile males was significantly lower than that of normospermic subjects (p=0.002). No significant difference was observed in serum neopterin, total oxidant, and malondialdehyde between the infertile and normospermic groups. Conclusion: The significant inverse correlation between seminal plasma neopterin and total antioxidant in the infertile males supports a possible role of neopterin in male infertility. Neopterin can be suggested as a marker in monitoring and diagnosis of idiopathic male infertility.